UTM's role in the development of Malaysian natural resources industries - Hassan, Azman; Kamal, Mohd. Nazlee; Yunan, Mat Hussin (1992)
Malaysia is blessed with abundance of natural resources such as oil, natural gas, minerals and fertile soil for planting palm, oil rubber, cocoa, timber and pepper. There is a bright outlook for the growth of both upstream and downstream industries based on natural resources in the country. The availability of skilled manpower and up-to-date technology are the important factors which determine the success of the industries. This paper highlights the role of Universiti Teknologi Malaysia (UTM) in developing the nation's natural resources industries especially in manpower training and research activities. A special emphasis will be given to the Faculty of Chemical and Natural Resources Engineering (FKKKSA) of UTM which is offering courses in petroleum, chemical, gas, polymer, bioprocess, and environmental engineering.